PENGARUH FAKTOR FINANSIAL (LEVERAGE, UKURAN PERUSAHAAN DAN PROFITABILITAS) TERHADAP PENGHINDARAN PAJAK SAAT MASA PANDEMI COVID-19 PADA PERUSAHAAN LQ 45 (Studi Empiris Laporan Triwulan II,III,IV 2020 Dan I,II 2021 Pada Perusahaan LQ 45 Yang Terdaftar Di BEI) - Rensi Dwi Maharani; Anik Malikah; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to find out how Financial Factors Effect (Leverage, Company Size And Profitability) On Tax Avoidance During Covid-19 Pandemic In Lq 45 Companies, either simultaneously or partially. All LQ 45 companies in quarter II, III, IV 2020-I, II 2021 were selected as the population, for sampling the researchers chose to use purposive sampling with certain criteria, and obtained 27 companies as samples. This research is classified as quantitative research and data collection uses the documentation method by collecting quarterly financial statements of each company, multiple linear regression analysis is the data analysis method in this study and the tests used are descriptive statistical tests, normality tests, classical assumption tests, and hypothesis testing. . The results of the study prove that Leverage, Company Size and profitability have a significant simultaneous effect on tax avoidance during the covid 19 pandemic, Leverage and Profitability partially affect tax avoidance during the COVID-19 pandemic, while company size does not partially affect tax avoidance during the COVID-19 pandemic.     Keywords: Leverage, company size, profitability and tax avoidance.